(untitled) (Global Journal of Medical Research, 2022)
In addition to biomatter, the human body includes a bioenergeme (personal component of organized bioenergemal energy; BEG) and also a possible third virtual (temporary, potential) component as well or biointerfaceme. From my experience regarding bioenergemal communication (BELC, relative to the BEG) practice with BEGs that are either at the BEL universe (where the BEGs arrive after the body biocollapses, dies)or at the biomaterial (BML) universe (space-time), it is possible to biocommunicate with human BEGs regarding topics of mutual interest, like the strike in the National Autonomous University of Mexico (UNAM, acronym in Spanish) 1999-2000. Of course, any BEG can establish BELC from the BEL universe to any BEG at the BML universe and vice versa or between themselves there or here. In the biodialogue that we establish through any relaxation validated technique, the bioimage of a BEG would be a living and acting virtual biointerfaceme, just like the rest of bioimages that are formed during it or in dreams.